Decolourisation of highly polluted palm oil mill biogas plant wastewater by using Ferric Chloride-Anionic Polyacrylamide - Dexter Zick Donny (2018)
The highly polluting palm oil mill biogas plant wastewater (POMBPW) can be treated using coagulation-flocculation process. In this preliminary study, the performance of several chemical coagulants i.e. ferric chloride, calcium lactate, magnesium hydroxide, aluminium chlorohydrate, and polydiallyldimethyl ammonium chloride (polyDADMAC) were investigated in removing the colour of POMBPW. The result shows that ferric chloride as a sole coagulant can achieve high colour removal of more than 80% without needing any pH adjustment, which indicates the effectiveness of the coagulant to treat POMBPW. The study was extended by incorporating flocculant i.e. polyDADMAC and polyacrylamide (PAM) with various charge to treat POMBPW by introducing it during slow mixing. Dual coagulants i.e. ferric chloride-anionic PAM (APAM) shows better performance than ferric chloride-polyDADMAC in terms of colour removal, pH, and sedimentation time. The addition of polymer to system not only reducing the ferric chloride concentration, but also increase the colour removal of more than 20%. Comparison between APAM and polyDADMAC as flocculant aids was carried out and it was found that APAM can achieve stable removal at wider pH range and the highest sedimentation time at 20 minutes while polyDADMAC was at one hour. Both dual coagulants were followed second order kinetic and APAM shows the highest rate over polyDADMAC i.e. 3×10-5/PtCo.min and 2×10-5/PtCo.min, respectively. The sludge generated from the coagulation-flocculation process has led to the environmental concern on how to dispose the sludge properly. The idea was to apply them as soil conditioner by evaluating them using phytotoxicity test. The sludge was filtered after all the flocs were settled down and was then dried and grinded. The water-soluble extracts were prepared with a mixing ratio of commercial soil and sludge at 1:1. Phytotoxicity result shows the problem of ferric chloride, however with addition of polymers, it improves the germination index value up to 80% which indicate the sludge was phytotoxin free and has potential to be reused for land application. Finally, another study of tri-coagulants was conducted which the aim was to reduce the usage of inorganic coagulant by introducing natural coagulant to the system i.e. ferric chloride-calcium lactate-APAM. However, the dominant coagulant was to be ferric chloride where it affect overall performance in decolourisation. Both calcium lactate and APAM were not have significant effect on the decolourisation regardless of the dosage applied. Nevertheless, APAM was able to produce larger flocs that can settle fast. Sand filtration was studied as post treatment and shows improvement in decolourisation. Apart from that, organic matters were also significantly removed from the treated water. Although sand filtration was the best choice for coagulation-flocculation post treatment, it still cannot produce crystal clear water and directly discharge into watercourse. In summary, the coagulation-flocculation process by using dual coagulants namely ferric chloride-anionic polyacrylamide was suitable to be applied for decolourisation of highly polluted palm oil mill biogas plant wastewater.